Types of Poetic Images in the Poem of Praise in the Two Collections of Ibn Al-Jiyab and Lisan Al-Din Ibn Al-Khatib (A Comparative Study) - Jassim, Baneen Abbas; Naima, Ali Mutasher (Journal of Ecohumanism, 2025)
This research monitors the diversity of poetic images in the poem of praise in the two collections of Ibn al-Jiyab and Lisan al-Din Ibn al-Khatib, describing it as a comparative study that attracted, through its artistic context and its various connotations related to sensory suggestions, the most prominent images in their poetry, between kinetic, color, scenic, and luminous images.